The Impact of Fiscal Policies on Inclusive Growth in Turkiye - Özgür Tonus; Bağdat Sıla Avcı (Journal of Economy Culture and Society)
Countries aim to inclusive growth to find a common solution the problems that poverty, income inequality, and unemployment. To boost inclusive growth, policies differ by country but fiscal policies play a crucial role in making growth more inclusive. In this study, five different indices were calculated to measure whether Turkish economic growth was inclusive. After obtaining the result that growth is inclusive, the calculated indices were used as the inclusive growth indicator, and we inquired in which direction the fiscal policies on education, health, social transfers, and taxes affect inclusive growth. Annual data covering the period 2006-2018, and the ARDL method were used to test the relationship between fiscal policies and inclusive growth. We figured out that fiscal policies had different effects on created inclusive growth indices. The results obtained show that public expenditures for health and education have a decreasing effect on inclusive growth indices while social transfers contributed positively to inclusive growth index, two indices were negatively affected by indirect taxes.